MENGURAI KOMPLEKSITAS STUNTING MELALUI PENDEKATAN COLLABORATIVE GOVERNANCE DI TINGKAT LOKAL - Setyo Nugroho; Sugiyanto (Social Welfare Study Program, 2026)
Abstract. Stunting is a multidimensional public policy issue influenced not only by health factors but also by social, economic, cultural, and governance dimensions. The sectoral approach that has traditionally dominated stunting interventions has not been sufficient to address its complex causes at the local level. This study aims to analyze the implementation of collaborative governance in stunting management by emphasizing the synergy among government institutions, communities, the private sector, and non-governmental organizations. A qualitative case study approach was employed to explore collaborative practices in local stunting governance. Data were collected through in-depth interviews, observations, and focus group discussions involving key stakeholders. Data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The findings reveal that the effectiveness of stunting management is strongly influenced by the quality of collaboration among stakeholders, particularly the clarity of roles, mutual trust, and effective coordination mechanisms. Collaborative governance enables the integration of cross-sectoral interventions, including health, education, sanitation, and social protection programs, resulting in more comprehensive and context-sensitive policy implementation. Furthermore, active community participation strengthens policy legitimacy and enhances program sustainability. This study concludes that collaborative governance provides an effective governance framework for addressing stunting at the local level. The findings imply the need to strengthen collaborative institutions, enhance the capacity of local actors, and develop adaptive and participatory coordination mechanisms to accelerate sustainable stunting reduction. The study contributes to the literature by highlighting collaborative governance as a strategic approach to managing complex public policy issues in local government. Keyword: Stunting; Collaborative Governance, Local Governance, Multi-Stakeholder Collaboration, Public Policy. Abstrak. Stunting merupakan permasalahan multidimensional yang dipengaruhi oleh faktor kesehatan, sosial, ekonomi, budaya, dan tata kelola pemerintahan. Pendekatan sektoral yang selama ini diterapkan dinilai belum mampu mengatasi kompleksitas permasalahan stunting secara optimal, sehingga diperlukan pendekatan kolaboratif yang melibatkan berbagai pemangku kepentingan. Penelitian ini bertujuan menganalisis implementasi collaborative governance dalam penanganan stunting di tingkat lokal dengan menekankan sinergi antara pemerintah, masyarakat, sektor swasta, dan lembaga non-pemerintah. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi, dan diskusi kelompok terarah (focus group discussion) yang melibatkan para pemangku kepentingan. Analisis data dilakukan secara interaktif melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa keberhasilan penanganan stunting sangat dipengaruhi oleh kualitas kolaborasi antaraktor yang ditandai dengan kejelasan pembagian peran, terbangunnya kepercayaan, serta mekanisme koordinasi yang efektif. Pendekatan collaborative governance mampu mengintegrasikan program lintas sektor, seperti kesehatan, pendidikan, sanitasi, dan perlindungan sosial, sehingga intervensi menjadi lebih komprehensif dan sesuai dengan kebutuhan lokal. Selain itu, partisipasi aktif masyarakat memperkuat legitimasi kebijakan sekaligus meningkatkan keberlanjutan program. Penelitian ini menyimpulkan bahwa collaborative governance merupakan strategi yang efektif dalam memperkuat tata kelola penanganan stunting di tingkat lokal. Oleh karena itu, diperlukan penguatan kelembagaan kolaboratif, peningkatan kapasitas aktor lokal, serta pengembangan mekanisme koordinasi yang adaptif dan partisipatif untuk mendukung percepatan penurunan stunting secara berkelanjutan. Kata Kunci: Stunting; Collaborative Governance, Tata Kelola Lokal, Kolaborasi Multi-Aktor, Kebijakan Publik.